Mengenang sepuluh tahun bencana industri lumpur Lapindo dan tindakan kolektif para korban - Sukamto Sukamto (Jurnal Teori dan Praksis Pembelajaran IPS, 2016)
This article aims to commemorate an extraordinary event called Industrial Disaster. This disaster occurred a long time, where the source bursts can not be stopped until now. Casualties are quite a lot, there is even a village wiped off the map, because the entire surface of the devastated hit by the mud. Settlement of sosial problems has just ended after the Government granted bail money as payment of "compensation". Compensation become a controversial term because basically what happens is buying and selling. Sure to two terms the consequences of each, which of course there are those who benefit the contrary there are also losers. Corporate parties are benefited while the victims were harmed.Keywords: Industrial Disaster, Lumpur Lapindo, Porong - Sidoarjo http://dx.doi.org/10.17977/um022v1i12016p052